In Vitro Clonal Propagation of Scoparia dulcis L., a Perennial Medicinal Herb (Bangladesh Journal of Scientific and Industrial Research, 2010)
An efficient protocol was established for in vitro clonal propagation of the perennial medicinal herb Scoparia dulcis L. (Family. Scrophulariaceae) through in vitro culture. Apical and axillary buds of young sprouts from selected plants were used as explants. Best shoot induction was observed on MS basal medium supplemented with 0.1 mg/l BAP, in which 94% of the explants produced 12 shoots per culture. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 16 shoots per culture. The half strength MS medium with 0.5 mg/l IBA +0.5 mg/l NAA the highest percentage (85.20) and maximum number (13.40) of roots were initiated within four weeks of culture. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 85%. Key words: Scoparia dulcis, Medicinal plant, Shoot proliferation, Micropropagation, Acclimatization, IAA (indoleacetic acid), IBA(indolebutanoic acid), NAA(α-naphthaleneacetic acid), BAP(benzylamino purine) DOI: 10.3329/bjsir.v44i3.4408 Bangladesh J. Sci. Ind. Res. 44(3), 341-346, 2009